SfDredd, a Novel Initiator Caspase Possessing Activity on Effector Caspase Substrates in Spodoptera frugiperda. - Zhouning Yang; Ke Zhou; Hao Liu; Andong Wu; Long Mei; Qingzhen Liu (PLoS ONE)
Sf9, a cell line derived from Spodoptera frugiperda, is an ideal model organism for studying insect apoptosis. The first notable study that attempted to identify the apoptotic pathway in Sf9 was performed in 1997 and included the discovery of Sf-caspase-1, an effector caspase of Sf9. However, it was not until 2013 that the first initiator caspase in Sf9, SfDronc, was discovered, and the apoptotic pathway in Sf9 became clearer. In this study, we report another caspase of Sf9, SfDredd. SfDredd is highly similar to insect initiator caspase Dredd homologs. Experimentally, recombinant SfDredd underwent autocleavage and exhibited different efficiencies in cleavage of synthetic caspase substrates. This was attributed to its caspase activity for the predicted active site mutation blocked the above autocleavage and synthetic caspase substrates cleavage activity. SfDredd was capable of not only cleaving Sf-caspase-1 in vitro but also cleaving Sf-caspase-1 and inducing apoptosis when it was co-expressed with Sf-caspase-1 in Sf9 cells. The protein level of SfDredd was increased when Sf9 cells were treated by Actinomycin D, whereas silencing of SfDredd reduced apoptosis and Sf-caspase-1 cleavage induced by Actinomycin D treatment. These results clearly indicate that SfDredd functioned as an apoptotic initiator caspase. Apoptosis induced in Sf9 cells by overexpression of SfDredd alone was not as obvious as that induced by SfDronc alone, and the cleavage sites of Sf-caspase-1 for SfDredd and SfDronc are different. In addition, despite sharing a sequence homology with initiator caspases and possessing weak activity on initiator caspase substrates, SfDredd showed strong activity on effector caspase substrates, making it the only insect caspase reported so far functioning similar to human caspase-2 in this aspect. We believe that the discovery of SfDredd, and its different properties from SfDronc, will improve the understanding of apoptosis pathway in Sf9 cells.